A study on public works department on the basis of key performance indicator regarding compliance to PPA 2006 & PPR 2008 in the procurement activities - Ahmed, Kazi Sharif Uddin (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.